Salt stress alters the spectrum of de novo mutation available to selection during experimental adaptation of Chlamydomonas reinhardtii. (5th September 2022) - Hasan, Ahmed R.; Lachapelle, Josianne; El‐Shawa, Sara A.; Potjewyd, Roman; Ford, Scott A.; Ness, Rob W.
Abstract: The genetic basis of adaptation is driven by both selection and the spectrum of available mutations. Given that the rate of mutation is not uniformly distributed across the genome and varies depending on the environment, understanding the signatures of selection across the genome is aided by first establishing what the expectations of genetic change are from mutation. To determine the interaction between salt stress, selection, and mutation across the genome, we compared mutations observed in a selection experiment for salt tolerance in Chlamydomonas reinhardtii to those observed in mutation accumulation (MA) experiments with and without salt exposure. MA lines evolved under salt stress had a single‐nucleotide mutation rate of 1.1 × 10 − 9 $1.1 × 10^{-9}$, similar to that of MA lines under standard conditions ( 9.6 × 10 − 10 $9.6 × 10^{-10}$ ). However, we found that salt stress led to an increased rate of indel mutations, but that many of these mutations were removed under selection. Finally, lines adapted to salt also showed excess clustering of mutations in the genome and the co‐expression network, suggesting a role for positive selection in retaining mutations in particular compartments of the genome during the evolution of salt tolerance. Our study shows that characterizing mutation rates and spectra expected under stress helps disentangle the effects of environment and selection during adaptation.